2003
DOI: 10.1021/es026185m
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Characterization of Arsenic in Ketza River Mine Tailings Using X-ray Absorption Spectroscopy

Abstract: Ketza River mine tailings deposited underwater and those exposed near the tailings impoundment contain approximately 4 wt % As. Column-leaching tests indicated the potential for high As releases from the tailings. The tailings are composed dominantly of iron oxyhydroxides, quartz, calcite, dolomite, muscovite, ferric arsenates, and calcium-iron arsenates. Arsenopyrite and pyrite are trace constituents. Chemical compositions of iron oxyhydroxide and arsenate minerals are highly variable. The XANES spectra indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
94
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 20 publications
13
94
3
2
Order By: Relevance
“…From this analysis as shown above, it was confirmed that this structure have water molecules, hydroxyl groups that were found to still exist even after heating the sample to > 600 °C (Figure 1). Therefore, based on all this vibrational evidence our preference for a "new"(similar to work by Moore & Ito, 1974) (Tyrrell & Graham, 1913;Jambor 1966;Ross & Post 1997;Pieczka et al, 1998;Paktunc et al, 2003Paktunc et al, , 2004Nishikawa et al, 2006;Becze and Demopoulos 2007;Walker et al, 2009;Garavelli et al, 2009). Finally, in this work it was observed that for arseniosiderite, and additional arsenate IR and Raman active vibrations occurred ~ 900 cm -1 indicative of protonated arsenate groups.…”
Section: Samplesupporting
confidence: 57%
See 3 more Smart Citations
“…From this analysis as shown above, it was confirmed that this structure have water molecules, hydroxyl groups that were found to still exist even after heating the sample to > 600 °C (Figure 1). Therefore, based on all this vibrational evidence our preference for a "new"(similar to work by Moore & Ito, 1974) (Tyrrell & Graham, 1913;Jambor 1966;Ross & Post 1997;Pieczka et al, 1998;Paktunc et al, 2003Paktunc et al, , 2004Nishikawa et al, 2006;Becze and Demopoulos 2007;Walker et al, 2009;Garavelli et al, 2009). Finally, in this work it was observed that for arseniosiderite, and additional arsenate IR and Raman active vibrations occurred ~ 900 cm -1 indicative of protonated arsenate groups.…”
Section: Samplesupporting
confidence: 57%
“…Arseniosiderite has been indicated to be more crystalline counter part of yukonite (Garavelli et al, 2009) and generally has slightly more calcium content in both natural and synthetic (Paktunc et al, 2003(Paktunc et al, , 2004Garavelli et al, 2009;Gomez et al, 2010a) samples then yukonite. More interesting, it was noted that the chemical formula commonly used in the literature (Paktunc et al, 2003(Paktunc et al, , 2004Fillipi et al, 2004Fillipi et al, , 2007Garavelli et al, 2009) Ca 2 Fe 3 (AsO 4 ) 3 O 2 ·3H 2 O had a peculiar form in that the use of peroxide types of molecular g r o u p s w e r e u s e d b u t a l s o n o h y d r o x y l g r o u p s w e r e i n c l u d e d i n t h e f o r m u l a s a s i n yukonite. Interestingly, most of these works where the formula was written in that fashion had no reference given to the earlier work of Moore and co-workers (Moore & Ito, 1974; (Burns & Hughes, 2003;Bastians et al, 2004).…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Neutral-alkaline conditions promote desorption of As bound to iron oxyhydroxides (Pierce and Moore, 1982) as well as dissolution of thermodynamically unstable iron and calcium arsenate minerals (Dove and Rimstidt, 1985;Paktunc et al, 2004). Arsenate mineral solubilities increase from ferric arsenates to calcium arsenates (Rochette et al, 1998;Paktunc et al, 2003). Both factors might account for the higher As release from the crusher material.…”
Section: Geochemical Controls On As Mobilisationmentioning
confidence: 99%